2019
DOI: 10.3389/fpsyg.2018.02707
|View full text |Cite
|
Sign up to set email alerts
|

Avian Emotions: Comparative Perspectives on Fear and Frustration

Abstract: Emotions are complex reactions that allow individuals to cope with significant positive and negative events. Research on emotion was pioneered by Darwin’s work on emotional expressions in humans and animals. But Darwin was concerned mainly with facial and bodily expressions of significance for humans, citing mainly examples from mammals (e.g., apes, dogs, and cats). In birds, emotional expressions are less evident for a human observer, so a different approach is needed. Understanding avian emotions will provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 152 publications
1
30
0
Order By: Relevance
“…The final five items also appear congruent with the theoretical account; according to the SCWM-R (Liu, 2011), frustration is a common psychological response among those who are exploring the issue of social inequality, whereas those who are unaware of the myth of meritocracy experience no particular psychological reaction to inequality. It is also consistent with the research that suggests that frustration is a psychological state closely related to reward omission and devaluation (Papini et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…The final five items also appear congruent with the theoretical account; according to the SCWM-R (Liu, 2011), frustration is a common psychological response among those who are exploring the issue of social inequality, whereas those who are unaware of the myth of meritocracy experience no particular psychological reaction to inequality. It is also consistent with the research that suggests that frustration is a psychological state closely related to reward omission and devaluation (Papini et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…However, many studies have found that amygdala is involved with many other negative emotions too, such as stress or anger (Siep et al, 2018), which might be due to the emotion flow: fear emotion is transient and can induce several other emotions, such as anger (Zheng et al, 2016). Animals under the influence of fear try to flight away from the threat, however, they will defend themselves, usually aggressively, when flight is impossible or difficult (Papini et al, 2018). This kind of “fight or flight” behavior or “fear and anger” emotion usually happens interchangeably (Zheng et al, 2016).…”
Section: Fmri Data On Basic Emotionsmentioning
confidence: 99%
“…Therefore, it is hard to say emotions are only neuromodulators separately or inseparately with behaviors. However, emotions can only be studied with these external expressions, such as physiological or behavioral changes, especially facial expressions, because we still cannot study animal emotions directly as we have no access to an organism’s subjective experience (Papini et al, 2018). Darwin was the first to use facial expressions in emotional studies, such as fear, anger, joy, or sadness.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the understanding of the phylogenetic continuity of the neural basis for emotions, it is important to elucidate the neural circuit that processes fear-related behaviours in animals other than mammals. Birds are animals that can potentially serve as models to analyse the control of fear-related reactions 5,6 . Indeed, lesions of the arcopallium/amygdala complex-a term that has been introduced by Herold et al, to describe a region that combines arcopallium, the posterior pallial amygdala, the nucleus taeniae of the amygdala (TnA) and subpallial amygdaloid area 7 -have been reported to reduce escape-and fear-related behaviour in birds [8][9][10] and many reports have suggested that a large region of the arcopallium/amygdala complex could be partially homologous to the mammalian amygdala 11,12 .…”
mentioning
confidence: 99%